Tanggung Jawab Sosial Dan Risiko Sistematis: Efek Moderasi Dari Fleksibilitas Keuangan Dan Investasi Penelitian Dan Pengembangan - Anita Anita; Lisa Lim (Jurnal Akademi Akuntansi, 2021)
The study is conducted with the aim of examining the effect of corporate social responsibility on systematic risk in companies listed on the IDX for the period of 2016-2020. This study adds financial flexibility and research and development investment as moderators which are still remain unexplored in Indonesia. This research is expected to be able to make investors consider social responsibility as a factor in making investment decisions. The data taken are stock prices, annual reports and sustainability reports which are secondary data. Data collection using purposive sampling method with certain criteria so that the number of samples in this study amounted to 43 companies. In testing the hypothesis using panel data regression analysis techniques with eviews. The results of the regression analysis show that the existence of corporate social responsibility has a significant positive effect on systematic risk. The moderating variable of financial flexibility does not affect the relationship between CSR and systematic risk. Then the research and development investment variables weaken the relationship between CSR and systematic risk. Therefore, management is expected to pay attention to R&D investment in making CSR policies. This study explains that R&D investment is one of the important roles in company sustainability.